Vitro and in silico antifungal efficacy of nitrogen- doped carbon nanohorn ( NCNH) against rhizoctonia solani - Dharni, Seema; Sanchita; Unni, SreeKuttan M.; Kurungot, Sreekumar; Samad, Abdul; Sharma, Ashok; Patra, Dharani Dhar (Journal of Biomolecular Structure & Dynamics, 2016)
We have investigated in vitro antifungal efficiency of nitrogen-doped carbon nanohorn (NCNH) against Rhizoctonia solani (R. solani) plant pathogenic fungi. NCNH with size of 50-60nm and concentrations of 10, 50, 100, and 150gmL(-1) were used. The results showed that growth of fungi in the presence of NCNH was significantly (p>.05) inhibited at 150gmL(-1) (85.13 +/-.97) after 72h. The results were validated through computational approaches. Molecular docking analysis of NCNH with endochitinase protein of R. solani was performed to validate the potential of antifungal activity of NCNH. Docking results showed different conformations of interaction of NCNH with endochitinase enzyme. The conformation with least binding energy -13.54kcal/mol was considered further. It is likely that NCNH interacts with the pathogens by mechanically wrapping, which may be one of the major toxicity actions of NCNH against R. solani. The analysis showed that NCNH might interwinds to endochitinase of R. solani leading to the deactivation of the enzyme. To best of our knowledge, this is the first report of antifungal efficacy of NCNH against R. solani and provides useful information about the application of NCNH in resisting crop disease.
Keywords: docking; endochitinase; nitrogen-doped carbon nanohorn; Rhizoctonia solani

TIAs pathway genes and associated miRNA identification in Vinca minor: supporting aspidosperma and eburnamine alkaloids linkage via transcriptomic analysis - Verma, Priyanka; Singh, Noopur; Khan, Shamshad Ahmad; Mathur, Ajay Kumar; Sharma, Ashok; Jamal, Farrukh (Physiology and Molecular Biology of Plants, 2020)
V. minorcontains monomeric eburnamine-type of indole alkaloids having utilization as a neuro-medicinal plant. The biosynthetic pathway studies using miRNAs has been the focal point for plant genomic research in recent years and this technique is utilized to get an insight into a possible pathway level study inV. minoras understanding of genes in this prized medicinal plant is meagrely understood. The de novo transcriptomic analysis using Illumina Next gen sequencing has been performed in glasshouse shifted plant and transformed roots to elucidate the possible non confirmed steps of terpenoid indole alkaloids (TIAs) pathway inV. minor. A putative TIA pathway is elucidated in the study including twelve possible TIAs biosynthetic genes. The specific miRNA associated with TIAs pathway were identified and their roles were discussed for the first time inV. minor. The comparative analysis of transcriptomic data of glasshouse shifted plant and transformed roots showed that the raw reads of transformed roots were higher (83,740,316) compared to glasshouse shifted plant (67,733,538). The EST-SSR prediction showed the maximum common repeats among glasshouse shifted plant and transformed roots, although small variation was found in trinucleotide repeats restricted to glasshouse shifted plant. The study reveals overall 37 miRNAs which were observed to be true and can have a role in pathway as they can regulate the growth and alkaloid production. The identification of putative pathway genes plays an important role in establishing linkage between Aspidosperma and Eburnamine alkaloids.
Keywords: de novo transcriptomic analysis; EST-SSR; miRNA; Terpenoid indole alkaloids; Vinca minor

BESFA: bioinformatics based evolutionary, structural & functional analysis of prostate, Placenta, Ovary, Testis, and Embryo (POTE) paralogs - Qazi, Sahar; Jit, Bimal Prasad; Das, Abhishek; Karthikeyan, Muthukumarasamy; Saxena, Amit; Ray, M. D.; Singh, Angel Rajan; Raza, Khalid; Jayaram, B.; Sharma, Ashok (Heliyon, 2022)
The POTE family comprises 14 paralogues and is primarily expressed in Prostate, Placenta, Ovary, Testis, Embryo (POTE), and cancerous cells. The prospective function of the POTE protein family under physiological conditions is less understood. We systematically analyzed their cellular localization and molecular docking analysis to elucidate POTE proteins' structure, function, and Adaptive Divergence. Our results suggest that group three POTE paralogs (POTEE, POTEF, POTEI, POTEJ, and POTEKP (a pseudogene)) exhibits significant variation among other members could be because of their Adaptive Divergence. Furthermore, our molecular docking studies on POTE protein revealed the highest binding affinity with NCI-approved anticancer compounds. Additionally, POTEE, POTEF, POTEI, and POTEJ were subject to an explicit molecular dynamic simulation for 50ns. MM-GBSA and other essential electrostatics were calculated that showcased that only POTEE and POTEF have absolute binding affinities with minimum energy exploitation. Thus, this study's outcomes are expected to drive cancer research to successful utilization of POTE genes family as a new biomarker, which could pave the way for the discovery of new therapies.
Keywords: (MMGBSA); Adaptive divergence; Evolution; generalized born surface area; Homology; Mechanics; Molecular docking; Molecular dynamic simulation molecular; POTE paralogs